Electrical impedance tomography measured at two thoracic levels can visualize the ventilation distribution changes at the bedside during a decremental positive end-expiratory lung pressure trial - Bikker, Ido G (BioMed Central, 2011)
INTRODUCTION: Computed tomography of the lung has shown that ventilation shifts from dependent to nondependent lung regions. In this study, we investigated whether, at the bedside, electrical impedance tomography (EIT) at the cranial and caudal thoracic levels can be used to visualize changes in ventilation distribution during a decremental positive end-expiratory pressure (PEEP) trial and the relation of these changes to global compliance in mechanically ventilated patients. METHODS: Ventilation distribution was calculated on the basis of EIT results from 12 mechanically ventilated patients after cardiac surgery at a cardiothoracic ICU. Measurements were taken at four PEEP levels (15, 10, 5 and 0 cm H(2)O) at both the cranial and caudal lung levels, which were divided into four ventral-to-dorsal regions. Regional compliance was calculated using impedance and driving pressure data. RESULTS: We found that tidal impedance variation divided by tidal volume significantly decreased on caudal EIT slices, whereas this measurement increased on the cranial EIT slices. The dorsal-to-ventral impedance distribution, expressed according to the center of gravity index, decreased during the decremental PEEP trial at both EIT levels. Optimal regional compliance differed at different PEEP levels: 10 and 5 cm H(2)O at the cranial level and 15 and 10 cm H(2)O at the caudal level for the dependent and nondependent lung regions, respectively. CONCLUSIONS: At the bedside, EIT measured at two thoracic levels showed different behavior between the caudal and cranial lung levels during a decremental PEEP trial. These results indicate that there is probably no single optimal PEEP level for all lung regions.